If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(5x+4)-11=3(2x-1)
We move all terms to the left:
2(5x+4)-11-(3(2x-1))=0
We multiply parentheses
10x-(3(2x-1))+8-11=0
We calculate terms in parentheses: -(3(2x-1)), so:We add all the numbers together, and all the variables
3(2x-1)
We multiply parentheses
6x-3
Back to the equation:
-(6x-3)
10x-(6x-3)-3=0
We get rid of parentheses
10x-6x+3-3=0
We add all the numbers together, and all the variables
4x=0
x=0/4
x=0
| 2(u+9)=-2(5u-1)+2u | | -10.3=w-58 | | 0.75x=-27 | | 9=-2x+23 | | -2/13x=-16.6 | | 2/3(-5+2x)-1/2=5 | | -3(-7w+9)-6w=7(w-4)-5 | | 0.5x+4=11 | | x÷2=48 | | 15t=16 | | 20r=12 | | x-3=7. | | 6v-2+2(4v+1)=-2(v+5) | | 12-5a=-7a+5 | | 4k/5-8/15=-4/3 | | 3w+4)(2w-1)=0 | | -2x+1/4=3/10 | | 3x-2+2x+3+34=180 | | 2x-2+2x+3+34=180 | | 5x+2+x+4=180 | | 0.2x=0.48 | | 6(5x-2)=42 | | 100/x+15=x | | 4-12-18x=-8x-10x | | 22-6x=-38 | | 870.8=1/3*3.14*8^2x | | 4-6(2-3×)=2x-(4-5x) | | 3÷7x=9 | | x=0.4*2x+0.4*1.2 | | x-0.8=0.48 | | 6(x-1)=7x+2-5(-3x-2) | | 5d-5=17 |